COMPARISON AS ONE OF THE STYLISTIC TROPES (SCIENCE TIME JOURNAL, 2023)
The given article deals with the stylistic trope comparison and methods of its formation. The aim of an article in the field of stylistics is to study the linguistic features of the stylistic method comparison in languages of different systems, in particular, in English and Karakalpak languages. The relevance of the research topic is due to the fact that there are still not enough works devoted to the study of stylistic trope and, in particular, such as comparison in languages of different systems, and this issue attracts the attention of linguists and is of great interest.